Effectiveness of the pelvic floor muscle training on muscular dysfunction and pregnancy specific urinary incontinence in pregnant women with gestational diabetes mellitus: A systematic review protocol - Pascon Barbosa, Angélica Mércia [UNESP]; Amador Enriquez, Eusebio Mario [UNESP]; Kron Rodrigues, Meline Rossetto; Prudencio, Caroline Baldini [UNESP]; Atallah, Álvaro Nagib; Abreu Reyes, David Rafael [UNESP]; Shetty Hallur, Raghavendra Lakshmana [UNESP]; Kenickel Nunes, Sthefanie [UNESP]; Pinheiro, Fabiane Affonso [UNESP]; Sartorão Filho, Carlos Isaías [UNESP]; Piemonte Andrade, Gabriela Lopes; Berghmans, Bary; et al. (Public Library of Science (PLoS), 2020)
Background There is ample evidence that gestational diabetes mellitus has a direct influence on urinary incontinence and pelvic floor muscles. There are no standardized pelvic floor muscle exercise programs in the literature for the physiotherapy and differ in the type of exercise, intensity, type and duration of application, and the frequency and duration of treatment sessions. The aim of this systematic review will be to investigate that Pelvic Floor Muscle Training can prevent and/or decrease the pregnancy specific urinary incontinence in women with gestational diabetes mellitus or gestational hyperglycemia. Methods We will perform a systematic review according to the Cochrane methodology of Randomized Controlled Trials. An overall search strategy will be developed and adapted for Embase, MEDLINE, LILACS, and CENTRAL databases, with the date of consultation until June 2020. The MeSH terms used will be Pregnancy, Hyperglycemia, Diabetes Mellitus, Type 2, Diabetes Mellitus, Type 1, Pregnancy in Diabetics, Diabetes, Gestational, Urinary Incontinence, Pelvic Floor Muscle Strength. Primary outcomes: improvement or cure of pregnancy specific urinary incontinence (which can be assessed by questionnaires, and tools such as tampon test, voiding diary, urodynamic study). Secondary outcomes: improvement of pelvic floor muscle strength (pelvic floor functional assessment, perineometer, electromyography, functional ultrasonography), improved quality of life (questionnaires), presence or absence of postpartum Urinary Incontinence and adverse effects. Quality assessment by Cochrane instrument. Metanalysis if plausible, will be performed by the software Review Manager 5.3. Discussion The present study will be the first to analyze the effectiveness of pelvic floor exercises in pregnant women with Gestational Diabetes Mellitus or Hyperglycemia, who suffer from pregnancy specific urinary incontinence. Randomized Controlled Trials design will be chosen because they present the highest level of evidence. It is expected to obtain robust and conclusive evidence to support clinical practice, in addition to promoting studies on the theme and contributing to new studies.